High Blood Pressure in a Urea Cycle Disorder: Case Report - Solé, Carolina; Arriaga, María; Cañedo, Elvira (American Journal of Perinatology Reports, 2020)
Introduction Urea cycle disorders (UCDs) form a group of metabolic pathological conditions that might develop serious neurological consequences. Early diagnosis, before irreversible damage is established, is the most important prognostic and morbidity factor.Case Report We present the case of a 5-day newborn with high blood pressure and respiratory distress. Diagnosis was type I citrullinemia. With appropriate citrullinemia guided-treatment blood pressure returned to normal.Conclusion High blood pressure has been rarely described as a lead symptom for the debut of a UCD. We must take this into consideration as an early recognition and treatment of these disorders are of the utmost importance.
Keywords: hypertension; citrullinemia; arginine; newborn